PENGARUH PEMBERIAN JENIS DAN KONSENTRASI AUKSIN TERHADAP INDUKSI PERAKARAN PADA TUNAS Dendrobium sp SECARA IN VITRO - Sulasiah, Anisah; Tumilisar, Christiani; Lestaria, Tuti (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Dendrobium orchids are the most widely grown because it has the advantages of easy to maintain and most easily grown. Induction of rooting in bud of Dendrobium sp by giving the different types and concentrations of auxin is one of many ways to get plantlets in large quantities and relatively quick time. The purpose of this research is to obtain the types and concentrations of auxin is the best in inducing rooting in bud of Dendrobium sp. This research was conducted at the Tissue Culture Laboratory, Department of Biology, Faculty of Mathematics and Science, State University of Jakarta on February to June 2013. The method used was description and experimental, the design of a factorial with two groups consisting of one control group and one experimental group for the provision of the types and concentrations of auxin on root induction in Dendrobium sp bud with each group consists three replications. Analysis of the data using three-way anova. Based on this research, Dendrobium sp bud induced by the different types and concentrations of auxin showed a distinct influence on the growth of bud in qualitative and quantitative characters. Qualitative data on root induction, shows that there is a root that grows one and two roots and shoots are green, white and brown. The results based on quantitative data showed that the bud of Dendrobium sp induced by auxin type 2,4-D and concentration of 0.75 ppm had an average number higher root length compared with the type of auxin IAA and NAA. Dendrobium sp bud are planted in the medium by the addition of auxin type of IAA and NAA at a concentration of 1.25 ppm has an average number of roots better than the auxin type 2,4-D. Keywords: Dendrobium sp, Types and Concentrations of Auxin, Rooting Induction